Several peripheral blood cells and the infection of sever acute respiratory syndrome coronavirus 2 - Jianwei Zhou; Cui Kong; Yin Sun (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
Blood routine is a common laboratory index in clinic, and used as an auxiliary item for diagnosing many diseases. Currently, sever acute respiratory syndrome coronavirus 2 (SARS-Cov-2) infection has been a pandemic concern which severely threatens human health [1]. Many clinicians and researchers around the world are focusing on the study of such an infection or the coronavirus disease (COVID-19) caused by the pathogen. Among the studies, the changes of Peripheral Blood Cells (PBC) belong to blood routine are generally investigated [2,3]. In the present report, we will overview the studies on the several PBC of the patients with SARS-Cov-2 infection.